2019
DOI: 10.1111/ecin.12760
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peer Presence on Cheating

Abstract: Recent research has shown that the presence of peers can increase individual output both in the lab and the field. This paper tests for negative side effects of such peer settings. We investigate whether peer settings are particularly prone to cheating even if they do not provide additional monetary benefits of cheating. Participants in our real-effort experiment had the opportunity to cheat when declaring their output levels. Although cheating did not have different monetary consequences when working alone th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 110 publications
(225 reference statements)
1
6
0
Order By: Relevance
“…When the die task is repeated, Rauhut (2013) showed that subjects who are told about others' reports lie more (less) when they underestimated (overestimated) others' lying behavior compared to uninformed subjects. Similar results were reported by Soraperra et al (2017) in a die task, by Robert and Arnab (2013) in the context of a sender-receiver game, and by Bäker and Mechtel (2019) and Lauer and Untertrifaller (2019) in real-effort experiments.…”
Section: Introductionsupporting
confidence: 85%
“…When the die task is repeated, Rauhut (2013) showed that subjects who are told about others' reports lie more (less) when they underestimated (overestimated) others' lying behavior compared to uninformed subjects. Similar results were reported by Soraperra et al (2017) in a die task, by Robert and Arnab (2013) in the context of a sender-receiver game, and by Bäker and Mechtel (2019) and Lauer and Untertrifaller (2019) in real-effort experiments.…”
Section: Introductionsupporting
confidence: 85%
“…Moreover, a competitive context-concerned with relative performance-plays a role on motivation, through the promotion of social comparison (Festinger, 1954). Bäker and Mechtel (2019) found more cheating when participants performed in the presence of a peer compared to working alone. Human values (Schwartz et al, 2012) are another set of important predictors (e.g., Pulfrey & Butera, 2013Pulfrey et al, 2019), as are perceived likelihood of being caught, severity of punishment, and difficulty-or accessibility-of cheating (e.g., Covey et al, 1989;Graham et al, 1994;Hollinger & Lanza-Kaduce, 1996;Houston, 1983;Shmeleva & Semenova, 2019;Zhao et al, 2021).…”
Section: From Individual To Collective Cheatingmentioning
confidence: 99%
“…Extrinsic motives (with external regulation, to employ Ryan & Deci's, 2000a taxonomy) such as academic or financial benefits, both for the whole group or for one of its members, were typically associated to competitive settings, steeped in social comparison (Festinger, 1954) and contextual pressures to perform and succeed. Interestingly, research showed that such settings do drive people to cheat in an individual or collective manner (e.g., Bäker & Mechtel, 2019;Cohen et al, 2009;Palazzo et al, 2012;Pulfrey & Butera, 2013;Pulfrey et al, 2018). Another instance of extrinsic motivation (in this case with introjected regulation, Ryan & Deci, 2000a) can be found in the social benefits mentioned by the participants.…”
Section: The Role Of Extrinsic Motivationmentioning
confidence: 99%
“…In Gino et al (2009), the presence of a confederate who signals the possibility to cheat increases individuals' dishonesty (see also Fosgaard et al, 2013). Information on the dishonesty of others increases lying (see Robert and Arnab (2013) in a sender-receiver game, Rauhut (2013) and Kroher and Wolbring (2015) in die games, Bäker and Mechtel (2019) and Lauer and Untertrifaller (2019) in real-effort tasks). In a field experiment on information transmission in networks, Drago et al (2020) showed that, on the other hand, informing targeted individuals on the risk of sanctions in case of detected fraud can generate large spillover effects on untreated neighbors.…”
Section: Related Literaturementioning
confidence: 99%